RNA-binding protein GIGYF2 orchestrates hepatic insulin resistance through STAU1/PTEN-mediated disruption of the PI3K/AKT signaling cascade - Ziwei Lv; Yuanyuan Ren; Yang Li; Fanglin Niu; Zhuozhuo Li; Man Li; Xiaofang Li; Qinhua Li; Deqing Huang; Yi Yu; Yuyan Xiong; Lu Qian (BMC, 2024)
Abstract Background Obesity is well-established as a significant contributor to the development of insulin resistance (IR) and diabetes, partially due to elevated plasma saturated free fatty acids like palmitic acid (PA). Grb10-interacting GYF Protein 2 (GIGYF2), an RNA-binding protein, is widely expressed in various tissues including the liver, and has been implicated in diabetes-induced cognitive impairment. Whereas, its role in obesity-related IR remains uninvestigated. Methods In this study, we employed palmitic acid (PA) exposure to establish an in vitro IR model in the human liver cancer cell line HepG2 with high-dose chronic PA treatment. The cells were stained with fluorescent dye 2-NBDG to evaluate cell glucose uptake. The mRNA expression levels of genes were determined by real-time qRT-PCR (RT-qPCR). Western blotting was employed to examine the protein expression levels. The RNA immunoprecipitation (RIP) was used to investigate the binding between protein and mRNA. Lentivirus-mediated gene knockdown and overexpression were employed for gene manipulation. In mice, an IR model induced by a high-fat diet (HFD) was established to validate the role and action mechanisms of GIGYF2 in the modulation of HFD-induced IR in vivo. Results In hepatocytes, high levels of PA exposure strongly trigger the occurrence of hepatic IR evidenced by reduced glucose uptake and elevated extracellular glucose content, which is remarkably accompanied by up-regulation of GIGYF2. Silencing GIGYF2 ameliorated PA-induced IR and enhanced glucose uptake. Conversely, GIGYF2 overexpression promoted IR, PTEN upregulation, and AKT inactivation. Additionally, PA-induced hepatic IR caused a notable increase in STAU1, which was prevented by depleting GIGYF2. Notably, silencing STAU1 prevented GIGYF2-induced PTEN upregulation, PI3K/AKT pathway inactivation, and IR. STAU1 was found to stabilize PTEN mRNA by binding to its 3'UTR. In liver cells, tocopherol treatment inhibits GIGYF2 expression and mitigates PA-induced IR. In the in vivo mice model, GIGYF2 knockdown and tocopherol administration alleviate high-fat diet (HFD)-induced glucose intolerance and IR, along with the suppression of STAU1/PTEN and restoration of PI3K/AKT signaling. Conclusions Our study discloses that GIGYF2 mediates obesity-related IR by disrupting the PI3K/AKT signaling axis through the up-regulation of STAU1/PTEN. Targeting GIGYF2 may offer a potential strategy for treating obesity-related metabolic diseases, including type 2 diabetes. Graphical Abstract